2004
DOI: 10.1207/s15548430jlr3603_3
|View full text |Cite
|
Sign up to set email alerts
|

The Effective Elementary Classroom Literacy Environment: Examining the Validity of the TEX-IN3 Observation System

Abstract: Here we report on the development and validation of an instrument that meets these two important criteria: a strong theoretical framework and a documented connection to student achievement growth. This instrument

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 13 publications
1
13
0
1
Order By: Relevance
“…Assessments currently being designed by the Smarter Balanced Assessment Consortium (SBAC, ) and the Partnership for Assessment of Readiness for College and Careers (PARCC, ) also promise to measure students' comprehension and analysis of texts of varied genres. This emphasis on reading and writing different kinds of texts aligns well with research suggesting that the breadth and quality of texts teachers use in their classrooms strongly relates to children's reading comprehension (Hoffman, Sailors, Duffy, & Beretvas, ). In one study, simply diversifying the types of text read and displayed in the classroom better supported first graders' writing of informational text (Duke, Martineau, Frank, Stebbe, & Bennett‐Armistead, ).…”
supporting
confidence: 77%
“…Assessments currently being designed by the Smarter Balanced Assessment Consortium (SBAC, ) and the Partnership for Assessment of Readiness for College and Careers (PARCC, ) also promise to measure students' comprehension and analysis of texts of varied genres. This emphasis on reading and writing different kinds of texts aligns well with research suggesting that the breadth and quality of texts teachers use in their classrooms strongly relates to children's reading comprehension (Hoffman, Sailors, Duffy, & Beretvas, ). In one study, simply diversifying the types of text read and displayed in the classroom better supported first graders' writing of informational text (Duke, Martineau, Frank, Stebbe, & Bennett‐Armistead, ).…”
supporting
confidence: 77%
“…We used a previously validated (Hoffman, Sailors, Duffy, & Beretvas, 2004 ) observation instrument that documented what the students and teacher were doing in the classroom. The instrument documented engagement with texts, using a framework close to an on-task perspective following the work of Stallings ( 1975 ) in the Follow Through studies.…”
Section: Observations Of Student Engagement and Active Teachingmentioning
confidence: 99%
“…Research has never shown that the program is more important than the teacher. Rather, we know that good teachers mold and modify the use of reading programs to their beliefs (Baumann & Heubach, ;Hoffman Sailors, Duffy, & Beretvas, ), and the most knowledgeable teachers can improve instruction even in the most scripted programs (Piasta et al, ). Excellent teachers must make moment‐by‐moment decisions to scaffold for their students.…”
Section: Closing Thoughtsmentioning
confidence: 99%